2021
DOI: 10.4081/monaldi.2021.1501
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary rehabilitation for cystic fibrosis: A narrative review of current literature

Abstract: Pulmonary rehabilitation is a key component in cystic fibrosis care.  This review summarizes the recent evidence in the area of pulmonary rehabilitation for cystic fibrosis in the form of questions and answers regarding interventions, indications, benefits and risks of pulmonary rehabilitation. Pulmonary rehabilitation includes airway clearance techniques, exercise training, education and behaviour change and can improve patients’ exercise capacity, muscle strength, quality of life and nutritional status. Airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
3
0
1
Order By: Relevance
“…In line with this, it was shown that the pwCF with a FEV1%pred < 40% were significantly less physically active compared to the pwCF with a FEV1%pred > 40% ( Table 4 ). Higher physical barriers might be related to the fear of pwCF of physical disadvantages of PA (e.g., dyspnea, exercise-induced bronchoconstriction) [ 24 ]. However, the overall safety of exercise or PA for pwCF was shown by Ruf et al who investigated adverse reactions during exercise testing and adverse reactions associated with exercise (e.g., pneumothorax).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, it was shown that the pwCF with a FEV1%pred < 40% were significantly less physically active compared to the pwCF with a FEV1%pred > 40% ( Table 4 ). Higher physical barriers might be related to the fear of pwCF of physical disadvantages of PA (e.g., dyspnea, exercise-induced bronchoconstriction) [ 24 ]. However, the overall safety of exercise or PA for pwCF was shown by Ruf et al who investigated adverse reactions during exercise testing and adverse reactions associated with exercise (e.g., pneumothorax).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of exercise and health, Williams (2016) found that cystic fibrosis ( CF ) patients who exercised for more than 30 min per day had fewer hospitalizations and improved lung function after 12 months compared to CF patients who exercised for less than 30 min per day. Kalamara et al (2021) also suggested that daily exercise can improve aerobic capacity and slow down the decline of lung function in CF patients, and a combination of aerobic and anaerobic training may be the best training approach for CF patients.…”
Section: Methodsmentioning
confidence: 99%
“…Es de aclarar, que estas patologías no se recomienda un entrenamiento muscular respiratorio aislado, sino combinado con entrenamiento aeróbico y ventilatorio, debido a las implicaciones sistémicas que tiene la enfermedad respiratoria crónica en niños (NE: 1++; GR: B). Esto coincide con lo expuesto Torres et al, (2019a) y Kalamara et al, (2021) quienes afirman que el entrenamiento muscular respiratorio se realiza en el marco de la rehabilitación pulmonar, la cual incluye el entrenamiento físico generalizado, el entrenamiento ventilatorio, acondicionamiento muscular periférico y respiratorio.…”
Section: Pereira Rodríguez and Curvelo Celedónunclassified